2017
DOI: 10.1186/s12872-017-0617-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine levels associated with a corrected QT interval

Abstract: BackgroundLittle is known about the relationship between homocysteine (Hcy) levels and the QT interval. We examined the association of different Hcy levels with corrected QT (QTc) intervals in a general population.MethodsPlasma levels of Hcy were assessed in a population-based study of 7002 participants 35 years of age and older from 2012 to 2013. Twelve-lead ECGs were performed on all participants and analyzed automatically.ResultsThe distribution of Hcy levels was determined for an entire population after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…They found the mean homocysteine levels among participants who had QTc > 440 ms were higher than those who had QTc 440 ms (p ¼ .031). However, this study showed that the prolonged QT was related to both high and low homocysteine levels [73]. Hyperhomocysteinemia can affect the synchronization of myocardial contraction, reflected by the prolongation of the QRS and QT interval on electrocardiogram.…”
Section: Uremic Toxinsmentioning
confidence: 59%
“…They found the mean homocysteine levels among participants who had QTc > 440 ms were higher than those who had QTc 440 ms (p ¼ .031). However, this study showed that the prolonged QT was related to both high and low homocysteine levels [73]. Hyperhomocysteinemia can affect the synchronization of myocardial contraction, reflected by the prolongation of the QRS and QT interval on electrocardiogram.…”
Section: Uremic Toxinsmentioning
confidence: 59%
“…In the present study, we demonstrated that even HHcy alone increased the risk of LVH. Our research team previously reported that higher plasma homocysteine levels were associated with a long QTc interval [33]. A long QTc interval is relevant to ventricular arrhythmia, which might result in sudden cardiac death [34].…”
Section: Discussionmentioning
confidence: 99%
“…The data collection and measurements used in this study were described in previous studies [ 10 , 12 14 ]. Data were collected via a single visit by experienced cardiologists and trained nurses, where a standard questionnaire was used by a face-to-face interview.…”
Section: Methodsmentioning
confidence: 99%